Grima: A Distinct Emotion Concept? - Schweiger Gallo, Inge; Fernández-Dols, José-Miguel; Gollwitzer, Peter M.; Keil, Andreas (Frontiers in Psychology, 2017)
People experience an unpleasant sensation when hearing a scratch on a board or plate. The present research focuses on this aversive experience known in Spanish as 'grima' with no equivalent term in English and German. We hypothesized that this aversive experience constitutes a distinctive, separate emotional experience. In Study 1, we found that the affective meaning of 'grima' was closer to 'asco' (i.e., 'disgust') than to other emotion concepts. Thus, in Study 2 we explored the features of grima and compared them with disgust. As grima was reported to be predominantly elicited by certain auditory stimuli and associated with a distinctive physiological pattern, Study 3 used direct measures of physiological arousal to test the assumption of a distinctive pattern of physiological responses elicited by auditory stimuli of grima and disgust, and found different effects on heart rate but not on skin conductance. In Study 4, we hypothesized that only participants with an implementation intention geared towards down-regulating grima would be able to successfully weaken the grima- but not disgust- experience. Importantly, this effect was specific as it held true for the grima-eliciting sounds only, but did not affect disgust-related sounds. Finally, Study 5 found that English and German speakers lack a single accessible linguistic label for the pattern of aversive reactions termed by Spanish speaking individuals as 'grima', whereas the elicitors of other emotions were accessible and accurately identified by German, English, as well as Spanish speakers.